Examining impact of inflation and inflation volatility on economic growth: Evidence from European Union economies - Anastasios Pappas; Nikolaos Boukas (Economies, 2025)
Examining the economies of the European Union from 2000 to 2023, we have found no strong evidence that the inflation rate has a negative impact on economic growth. In contrast, in line with conventional economic theory, higher interest rates are associated with lower economic growth. The results remain consistent even after controlling for various control variables, non-linearities and endogeneity issues. These findings suggest that an aggressive tightening of monetary policy in the euro area, aimed at rapidly bringing inflation under control, could actually be detrimental to economic growth. Since the negative effects of monetary tightening on growth are clear, while the benefits of rapidly reducing inflation on economic growth are ambiguous, the European Central Bank must be cautious about both the intensity and the duration of monetary tightening.
Keywords: E31; E40; E52; E58; O40; 330; economic growth; inflation; inflation volatility; interest rates; European Union; panel data